Topics in Applied Statistics 2012 Symposium of the International Chinese Statistical Association - Hu, Mingxiu; Liu, Yi; Lin, Jianchang (Springer Proceedings in Mathematics & Statistics,, 2013)
The 21st ICSA Applied Statistics Symposium took place between the 23rd and 26th of June, 2012 in Boston, Massachusetts. The Symposium was co-sponsored by the International Society for Biopharmaceutical Statistics (ISBS) and American Statistical Association (ASA). This is the first proceedings volume to share research from the ICSA Applied Statistics Symposium. The volume consists of 27 selected papers from topics that range from statistical applications in business and finance to applications in clinical trials and biomarker analysis. All papers feature original, peer-reviewed content. The editors intentionally selected papers as broad as possible to serve the whole statistical community and the vast variety in research interests.